Cover Image. Issue 8 (28th July 2017) - Sunadome, H.; Matsumoto, H.; Petrova, G.; Kanemitsu, Y.; Tohda, Y.; Horiguchi, T.; Kita, H.; Kuwabara, K.; Tomii, K.; Otsuka, K.; Fujimura, M.; Ohkura, N.; et al.
Abstract : The cover image, by H. Sunadome et al., is based on the Original Article IL4Rα and ADAM33 as genetic markers in asthma exacerbations and type‐2 inflammatory endotype, DOI10.1111/cea.12927